Dimensionality and reliability of the Depression Anxiety Stress Scales 21 among adolescents in North Macedonia - Naumova, Katerina (Frontiers in Psychology, 2022)
This study examined the structural validity and reliability of the DASS-21 in a large sample (N = 4202) of secondary school students from North Macedonia (Mage = 16.43±1.04, 65% girls). Based on theoretical and empirical considerations, five structural models were compared using confirmatory factor analysis. The original three-factor model provided good fit to the data; however, high interfactor correlations indicated that the depression, anxiety, and stress factors were indistinguishable. The bifactor solution yielded superior fit relative to other tested models. Factor loading patterns revealed a strong general factor and some specificity of the depression and anxiety factors, whereas the stress items were primarly markers of general distress. Model-based reliability and ancillary bifactor indices revealed that the DASS-21 is essentially unidimensional. Thus, only the total score could be used as a reliable measure of general emotional distress, while subscale scores should be avoided. Overall, the findings provide further support for the cross-cultural validity of the DASS-21 and confirm that it is suitable for use among older adolescents in North Macedonia.